2012
DOI: 10.1136/bmj.e5287
|View full text |Cite
|
Sign up to set email alerts
|

Kidney stones and kidney function loss: a cohort study

Abstract: Objective To investigate whether the presence of kidney stones increase the risk of end stage renal disease (ESRD) or other adverse renal outcomes.Design A registry cohort study using validated algorithms based on claims and facility utilisation data. Median follow-up of 11 years.Setting Alberta, Canada, between 1997 and. Participants 3 089 194 adult patients without ESRD at baseline or a history of pyelonephritis. Of these, 1 954 836 had outpatient serum creatinine measurements and were included in analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
4
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(210 citation statements)
references
References 23 publications
7
190
4
9
Order By: Relevance
“…The rising incidence of nephrolithiasis among younger girls also has important public health implications. Controlling for comorbidities, medications, body mass index, and diet, nephrolithiasis is associated with an increased risk of CKD, cardiovascular disease, and fracture, with the greatest risks observed among younger women (1)(2)(3). Although these associations may not be causal, it is likely that the risks for and burden of these diseases will be greater for patients who develop nephrolithiasis earlier in life because of a longer lifetime over which kidney, heart, and bone diseases may develop.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The rising incidence of nephrolithiasis among younger girls also has important public health implications. Controlling for comorbidities, medications, body mass index, and diet, nephrolithiasis is associated with an increased risk of CKD, cardiovascular disease, and fracture, with the greatest risks observed among younger women (1)(2)(3). Although these associations may not be causal, it is likely that the risks for and burden of these diseases will be greater for patients who develop nephrolithiasis earlier in life because of a longer lifetime over which kidney, heart, and bone diseases may develop.…”
Section: Discussionmentioning
confidence: 96%
“…Kidney stone disease (nephrolithiasis) is a systemic metabolic disorder associated with increased risks of cardiovascular disease and CKD in adults and fracture in children and adults (1)(2)(3), and it has annual costs .$5.1 billion (4). The estimated prevalence of nephrolithiasis in the United States increased from 5.2% (1988)(1989)(1990)(1991)(1992)(1993)(1994)) to 8.8% (2007)(2008)(2009)(2010) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…As part of the ARIC study visit 3, but not at visit 4, participants were asked whether a doctor had ever told them that they had kidney stones diagnosed by a physician. In addition, inpatient encounters that involved stone disease were identified through ARIC surveillance between 1987 and 2010 by the following International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes on hospital discharge summaries: 592 (calculus of the kidney and ureter), 592.0 (calculus of kidney), 592.1 (calculus of ureter), 592.9 (urinary calculus, unspecified), 594 (calculus of lower urinary tract), and 274.11 (uric acid nephrolithiasis), consistent with codes used in previous cohort studies (22,23). Because these captured only inpatient encounters, we also queried linked data from the US Centers for Medicare and Medicaid Services (CMS) for the same ICD-9-CM codes.…”
Section: Assessment Of Kidney Stonesmentioning
confidence: 69%
“…In crosssectional studies, a history of kidney stones was associated with lower GFR and greater prevalence of CKD (20,21). Two prospective cohort studies from the Mayo Health System and the Alberta Kidney Disease Network demonstrated a higher risk of incident CKD in persons with a history of stone disease (22,23). However, both prospective studies involved universally insured and homogenous populations (96%-99% white) (22,24), thus limiting the generalizability of these findings.…”
Section: Introductionmentioning
confidence: 90%
“…ESRD unadjusted rate was 2.48 per million people per day in people with one or more episodes of kidney stones compared to 0.52 per million people per day in the people without kidney stones. 8 Kidney stone is a common clinical problem and potentially preventable, therefore, accurate assessment and prompt intervention is required. Histopathologic findings found by post surgical biopsy and microscopic examination may be important to predict residual renal function and long-term outcome.…”
Section: Introductionmentioning
confidence: 99%